A bifunctional catalyst containing silicon-modified low-silica ZSM-5 molecular sieve and application thereof in synthesis gas to aromatic hydrocarbon reaction
Patent Information
- Application Number
- CN202510429494.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-08
- Publication Date
- 2026-10-16
AI Technical Summary
金属氧化物与ZSM-5分子筛的复合催化剂能够实现合成气直接制芳烃,但是其中BTX的选择性很低,仅约为30%
[0018]1、本发明与传统的费托合成制液体燃料不同,实现了一步直接将合成气高效转化为芳烃,同时芳烃中BTX的选择性达到60%。
Smart Images

Figure BDA0005347715090000041 
Figure BDA0005347715090000051 
Figure BDA0005347715090000061
Abstract
Description
Technical Field
[0001] This invention pertains to the production of aromatics from syngas, specifically relating to a bifunctional catalyst containing silicon-modified ZSM-5 molecular sieve with a low silicon-to-aluminum ratio and its application in the syngas-to-aromatics reaction. Background Technology
[0002] Benzene, toluene, and xylene (collectively known as BTX) are fundamental products and raw materials in the petrochemical industry, widely used in the production of synthetic materials such as polyurethane and polyester, as well as chemical products such as synthetic fibers, plastics, and rubber. In addition, aromatics are used as gasoline blending components and in the production of pesticides, herbicides, pharmaceuticals, and dyes. Currently, aromatics are a major product of my country's petrochemical industry, and large-scale industrial production of BTX relies heavily on petroleum, with over 70% of BTX originating from naphtha reforming. Although my country's aromatics production capacity has increased significantly in recent years, reaching a certain scale, it still cannot meet actual market demand. my country's dependence on imported xylene has reached 60%. Furthermore, in the past two years, the production capacity of downstream benzene products in my country has grown rapidly, especially with the large-scale construction of styrene, aniline, phenol, and cyclohexanone production facilities, leading to a surge in benzene market demand, which domestic production cannot meet. Due to my country's energy supply situation of "abundant coal, scarce oil, and limited gas," my country heavily relies on imported oil. With the rapid development of my country's economy, the demand for crude oil has increased year by year, and currently, the dependence on imported crude oil exceeds 65%. Given the dwindling global oil resources and persistently high crude oil prices, developing new processes for aromatics production that do not rely on oil resources, and producing aromatics from non-oil resources such as coal, natural gas, and biomass, will be of significant strategic importance.
[0003] my country has abundant coal resources. Using coal as raw material, it can be gasified into syngas (a mixture of CO and H2), and then used to produce aromatics from non-petroleum resources. Composite catalysts of metal oxides and ZSM-5 molecular sieves can achieve direct syngas-to-aromatics production, but the selectivity for hydroxyl radicals (BTX) is very low, only about 30%. In 2017, Cheng et al. used Zn-ZrO2 coupled with ZSM-5 molecular sieves (SiO2 / Al2O3 ratio of 120) to increase CO conversion to 20% and aromatics selectivity to 80%, but the BTX selectivity was only 21.9%. In 2020, Miao et al. improved BTX selectivity by shielding the acidic sites on the outer surface of ZSM-5 molecular sieves with a high silica-to-alumina ratio (SiO2 / Al2O3 ratio of 146), increasing the proportion of BTX components in light aromatics to 69.6%. However, silicon deposited on the outer surface reduces the total number of acidic sites and active sites, and can partially clog pores, leading to decreased CO conversion, reduced aromatic selectivity, and lower catalyst efficiency. In 2021, Xu et al. also used Si to shield the acidic sites on the outer surface of ZSM-5 molecular sieves with a high silicon-to-aluminum ratio (SiO2 / Al2O3 of 80 to 200) to improve BTX selectivity, but it was difficult to simultaneously achieve high CO conversion, high aromatic selectivity, and high BTX selectivity. Therefore, developing a process for directly producing high BTX selectivity from syngas is of great significance for alleviating the shortage of aromatics supply in my country and for the energy, chemical fiber, textile, and plastics industries. Summary of the Invention
[0004] To address the above problems, this invention provides a bifunctional catalyst of silicon-modified ZSM-5 molecular sieve with a low silicon-to-aluminum ratio and its application in the synthesis of aromatics from syngas.
[0005] To achieve the above objectives, the technical solution of the present invention is as follows:
[0006] This invention provides a bifunctional catalyst containing a silicon-modified ZSM-5 molecular sieve with a low silicon-to-aluminum ratio, characterized in that: the catalyst comprises component I and component II, wherein the active component of component I is a metal oxide, and component II is a silicon-modified ZSM-5 molecular sieve with a low silicon-to-aluminum ratio; and components I and II are mechanically mixed together.
[0007] The chemical formula of the metal oxide is MnCr. y O (x+1.5y) MnAl y O (x+1.5y) MnZr y O (x+2y) MnIn y O (x+1.5y) ZnCr y O(1+1.5y) ZnAl y O (1+1.5y) ZnGa y O (1+1.5y) ZnIn y O (2+1.5y) CoAl y O (1+1.5y) ,FeAl y O (1+1.5y) In y Al z MnO (x+1.5y+1.5z) In y Ga z MnO (x+1.5y+1.5z) One or more of the following, wherein x is 1–3.5, y is 0.1–10, and z is 0.1–10; the specific surface area of the oxide is 30–150 m². 2 / g;
[0008] The SiO2 / Al2O3 ratio of the silicon-modified low Si / Al ratio ZSM-5 molecular sieve of component II is 25-80, preferably 30-50;
[0009] The silicon-modified low-silica-alumina ratio ZSM-5 molecular sieve exhibits moderately strong acidity, with the amount of moderately strong acid sites ranging from 0.3 to 0.55 mol / kg. The temperature range corresponding to the peak apex of the NH3-TPD desorption peak for the moderately strong acid is 200-500℃. Acetone is used as a probe molecule. 13 The C-NMR chemical shift is in the range of 210-220 ppm.
[0010] The acid strength is defined by the NH3-TPD peak, encompassing three acidities: weak acid, moderately strong acid, and strong acid. The NH3-TPD is based on the desorption peak position of NH3. This desorption peak position refers to the position of the desorbed NH3 thermal conductivity signal recorded by a TCD under standard test conditions: a sample mass w to carrier gas flow rate f ratio (w / f) = 100 g·h / L, and a heating rate of 10℃ / min. The desorption curve is plotted, and the inorganic solid is classified into three acid strengths based on the peak position of the curve. Weak acid refers to acid sites with an NH3 desorption temperature below 275℃; moderately strong acid refers to acid sites with an NH3 desorption temperature between 275-500℃; and strong acid refers to acid sites with an NH3 desorption temperature above 500℃.
[0011] Based on the above technical solutions, preferably, the weight ratio of the active ingredient in component I to component II is 0.1-20; more preferably, it is 0.3-5.
[0012] Based on the above technical solutions, preferably, the powder mixing method of component I and component II is to mix component I and component II by grinding, ball milling or other methods, and to achieve uniform mixing by utilizing the extrusion force, impact force, shearing force, friction force or other effects generated by the movement of materials and / or containers.
[0013] Based on the above technical solution, preferably, component I further includes a dispersant, wherein the metal oxide is dispersed in the dispersant; the dispersant is Al2O3, SiO2, or Cr2O. 3、 One or more of ZrO2, TiO2, Ga2O3, activated carbon, graphene, and carbon nanotubes;
[0014] Based on the above technical solution, preferably, the content of dispersant in component I is 0.05-90wt%, preferably 0.05-25wt%, and the remainder is the metal oxide.
[0015] Based on the above technical solutions, preferably, the silicon source for the silicon-modified low silica-to-alumina ratio ZSM-5 molecular sieve of component II is one or more of polysiloxane, water glass, sodium silicate, and tetraethyl orthosilicate. The silicon source is used to modify the surface of the ZSM-5 molecular sieve through specific processes (such as impregnation, coating, etc.).
[0016] This invention provides the application of the above-mentioned catalyst in the synthesis of aromatics from syngas. Syngas is used as the reactant, and the syngas is an H2 / CO mixture. Aromatics are produced by a conversion reaction in a fixed bed or moving bed under the action of the catalyst. The H2 / CO molar ratio of the syngas is 0.2-3.5; the reaction pressure is 0.5-10 MPa; the reaction temperature is 300-600℃; and the reaction space velocity is 300-12000 h⁻¹. -1 .
[0017] Based on the above technical solution, preferably, the aromatic selectivity of the reaction process can reach 60-80%, the selectivity of BTX in aromatics can reach 60%, and the selectivity of the byproduct methane is less than 8%. This invention has the following beneficial effects:
[0018] 1. Unlike traditional Fischer-Tropsch synthesis for producing liquid fuels, this invention achieves a one-step direct and efficient conversion of syngas into aromatics, with a selectivity of 60% for BTX in the aromatics.
[0019] 2. In this invention, after component II is modified with silicon, side reactions such as olefin hydrogenation and long-chain hydrocarbon cracking on the molecular sieve are effectively suppressed, greatly improving the selectivity of BTX.
[0020] 3. Using either component I or component II alone cannot achieve the functions of this invention. For example, using component I alone results in very high methane selectivity and very low conversion rate, while using component II alone is almost ineffective in activating and converting syngas. Only synergistic catalysis of components I and II can achieve efficient syngas conversion and obtain excellent selectivity. This is because component I can activate syngas to generate specific reactive gas-phase intermediates. These intermediates diffuse into the pores of component II via the gas phase. Due to the unique properties of the silicon-modified ZSM-5 molecular sieve selected in this invention, the reactive gas-phase intermediates generated by component I can be effectively further activated and converted into aromatics.
[0021] 4. The composite catalyst in this invention has a simple preparation process and mild conditions; and the reaction process has a high product yield and selectivity, with an aromatic selectivity of 60-80% and a BTX selectivity of 60% in aromatics, while the byproduct methane selectivity is less than 8%. Detailed Implementation
[0022] The present invention will be further illustrated below by way of embodiments, but the scope of the claims of the present invention is not limited to these embodiments. Furthermore, the embodiments only provide some conditions for achieving this objective, but do not imply that these conditions must be met to achieve this objective.
[0023] The specific surface area of a sample can be tested by physical adsorption of nitrogen or argon.
[0024] I. Preparation of Catalyst Component I
[0025] The metal oxide in catalyst component I of this invention can be obtained by purchasing commercially available metal oxides with high specific surface area, or by the following methods:
[0026] Precipitation method for synthesizing MnCr with high specific surface area y O (x+1.5y) MnAl y O (x+1.5y) MnZr y O (x+2y) MnIn y O (x+1.5y) ZnCr y O (1+1.5y) ZnAl y O (1+1.5y) ZnGa y O (1+1.5y) ZnIn y O (2+1.5y) CoAl y O (1+1.5y) ,FeAl y O (1+1.5y)In y Al z MnO (x+1.5y+1.5z) In y Ga z MnO (x+1.5y+1.5z) :
[0027] Zinc nitrate, aluminum nitrate, chromium nitrate, manganese nitrate, zirconium nitrate, indium nitrate, cobalt nitrate, and ferric nitrate were used as precursors and mixed with ammonium carbonate in water at room temperature (ammonium carbonate was used as a precipitant, and the feeding ratio was either ammonium carbonate in excess or preferably ammonium ions to metal ions in a 1:1 ratio). The mixture was aged, then washed, filtered, and dried. The resulting solid was calcined in air to obtain metal oxides with high specific surface area. The specific samples and their preparation conditions are shown in Table 2 below.
[0028] Table 1. Preparation and performance parameters of high specific surface area metal oxides
[0029]
[0030]
[0031] II. Preparation of Catalyst Component II (Silicon-Modified Low-Silica-Alumina Ratio ZSM-5 Molecular Sieves)
[0032] The moderately strong acids described in this invention can be tested using methods such as solid-state NMR spectroscopy (H-N), NH3-TPD, infrared spectroscopy, and chemical titration. However, the methods for testing acidity are not limited to those described above.
[0033] Component II described in this invention can be a commercially available ZSM-5 molecular sieve with an acid density that meets the requirements of this invention, or it can be a self-synthesized molecular sieve. Here, we take a low-silicon-aluminum ratio ZSM-5 molecular sieve prepared by hydrothermal synthesis as an example.
[0034] The specific preparation process of ZSM-5 molecular sieve with low silica-to-alumina ratio is as follows:
[0035] Raw materials were weighed according to the following molar ratio: SiO2:Al2O3:TPAOH:H2O = 1:0.04-0.0125:0.4:45: silicon source, aluminum source, tetrapropylammonium hydroxide, and deionized water. The mixture was stirred at room temperature for 2 hours, then transferred to a hydrothermal reactor and crystallized at 160-180℃ for 4-7 days. The mixture was then rapidly cooled to room temperature in a water bath and repeatedly centrifuged and washed until the pH of the supernatant was 7 at the end of the washing process. The precipitate was dried at 110℃ for 12 hours and then calcined in air at 600℃ for 3 hours to obtain ZSM-5 molecular sieve.
[0036] The silicon source is selected from one or more of TEOS, silica sol, and silica; the aluminum source is selected from one or more of sodium aluminate, Al(OH)3, AlOOH, and aluminum isopropoxide.
[0037] The framework element composition of the ZSM-5 molecular sieve can be one or more of the following: Si-O, Si-Al-O, Si-BO, Si-Al-Ti-O, Ga-Si-O, Ga-Si-Al-O, Mg-Al-PO, Fe-Si-O, and As-Si-O.
[0038] The specific preparation process for silicon modification is as follows:
[0039] A certain amount of silicon source and hexane (solvent) were mixed evenly, and then ZSM-5 molecular sieve with low silicon-to-aluminum ratio was added. The mixture was stirred dry at room temperature, dried at 110℃ for 12 hours, and then calcined in air at 550℃ for 4 hours to obtain silicon-modified ZSM-5 molecular sieve with low silicon-to-aluminum ratio.
[0040] Table 2. Preparation and performance parameters of low silica-alumina ratio ZSM-5 molecular sieves.
[0041]
[0042] III. Catalyst Preparation
[0043] The required proportions of the above-obtained components I and II are added to the container. The separation, crushing, and mixing are achieved by utilizing one or more of the extrusion force, impact force, shearing force, and friction force generated by the high-speed movement of these materials and / or the container. The conversion of mechanical energy, thermal energy, and chemical energy is achieved by adjusting the temperature and carrier gas atmosphere, and the interaction between different components is further regulated.
[0044] During mechanical mixing, the mixing temperature can be set to 20-100℃, and the process can be carried out in an atmosphere or directly in air, with the atmosphere selected from any of the following gases:
[0045] a) Nitrogen and / or inert gases;
[0046] b) A mixture of hydrogen and nitrogen and / or inert gases, wherein the volume of hydrogen in the mixture is 5 to 50%;
[0047] c) A mixture of CO with nitrogen and / or an inert gas, wherein the volume of CO in the mixture is 5 to 20%;
[0048] d) A mixture of O2 and nitrogen and / or an inert gas, wherein the volume of O2 in the mixture is 5-20%, and the inert gas is one or more of helium, argon, and neon.
[0049] Mechanical mixing can be achieved by combining one or more of the following methods: mechanical stirring, shaking table mixing, etc.
[0050] Mechanical stirring: In a stirring tank, component I and component II are mixed using a stirring rod. By controlling the stirring time (5 min-120 min) and speed (30-300 rpm), the degree of mixing and the relative distance between component I and component II can be adjusted.
[0051] Ball milling: Utilizes the high-speed tumbling of abrasive and catalyst within a grinding jar to generate strong impact and crushing on the catalyst, achieving the dispersion and mixing of component I and component II. By controlling the ratio of abrasive (materials can be stainless steel, agate, or quartz; size range: 5mm-15mm) to catalyst (mass ratio range: 20-100:1), the particle size and relative distance of the catalyst can be adjusted.
[0052] Shaking method: Premix component I and component II and put them into a container; mix component I and component II by controlling the reciprocating or circular oscillation of the shaker; achieve uniform mixing and adjust their relative distance by adjusting the oscillation speed (range: 1-70 rpm) and time (range: 5 min-120 min).
[0053] Mechanical grinding method: Premix component I and component II and put them into a container; under a certain pressure (range: 5 kg-20 kg), the mixture is subjected to relative motion (speed range: 30-300 rpm) with the grinding tool to adjust the particle size and relative distance of the catalyst and achieve uniform mixing.
[0054] The specific catalyst preparation and its parameter characteristics are shown in Table 3.
[0055] Table 3. Preparation and parameter characteristics of catalysts
[0056]
[0057]
[0058] IV. Examples of Catalytic Reactions
[0059] The composite catalyst prepared above was loaded into a fixed-bed reactor equipped with a gas mass flow meter and an online product analysis chromatograph (the tail gas of the reactor was directly connected to the quantitative valve of the chromatograph for periodic real-time sampling and analysis).
[0060] 2g of the catalyst of the present invention was placed in a fixed-bed reactor. The air in the reactor was replaced with Ar, and then the temperature was raised to 300°C. The synthesis gas was switched (H2 / CO molar ratio = 1) at a pressure of 4MPa. The temperature was raised to the reaction temperature of 430°C, and the space velocity of the reactant gas was adjusted to 2500mL / g / h. The product was analyzed by online chromatography.
[0061] Table 4 lists the specific applications of the catalysts and their effect data.
[0062] Table 4. Specific applications and effect data of catalysts.
[0063]
[0064] In Comparative Example 1, component II in the catalysis was a low silica-to-alumina ZSM-5 molecular sieve without silicon modification, and its selectivity for BTX in aromatics was only 30%.
[0065] In Comparative Example 2, component II in the catalysis was a ZSM-5 molecular sieve with a medium-strong acid content of less than 0.3 mol / kg, which had a low conversion rate of only 7% and a low aromatic selectivity of 51%.
[0066] The catalyst in Comparative Example 3 contained only component I, had an extremely low conversion rate, and produced no aromatics.
[0067] The results above show that the matching between catalyst components I and II and the mixing method of the components are crucial, directly affecting the conversion rate of carbon monoxide, the selectivity of aromatics, and the proportion of BTX.
[0068] The above description is merely a few embodiments of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any modifications or alterations made by those skilled in the art without departing from the scope of the technical solution of the present invention using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A bifunctional catalyst containing a surface-modified ZSM-5 molecular sieve with a low silica-to-alumina ratio, characterized in that: The catalyst comprises component I and component II, wherein the active component of component I is a metal oxide and component II is a silicon-modified ZSM-5 molecular sieve with a low silica-to-alumina ratio; component I and component II are combined together by mechanical mixing. The chemical formula of the metal oxide is MnCr. y O (x+1.5y) MnAl y O (x+1.5y) MnZr y O (x+2y) MnIn y O (x+1.5y) ZnCr y O (1+1.5y) ZnAl y O (1+1.5y) ZnGa y O (1+1.5y) ZnIn y O (2+1.5y) CoAl y O (1+1.5y) ,FeAl y O (1+1.5y) In y Al z MnO (x+1.5y+1.5z) In y Ga z MnO (x+1.5y+1.5z) One or more of the following, wherein x is 1–3.5, y is 0.1–10, and z is 0.1–10; the specific surface area of the oxide is 30–150 m². 2 / g; The SiO2 / Al2O3 ratio of the silicon-modified low Si / Al ratio ZSM-5 molecular sieve of component II is 25-80, preferably 30-50; The silicon-modified low silica-alumina ratio ZSM-5 molecular sieve has medium-strong acidity, with the amount of medium-strong acid sites being 0.3-0.55 mol / kg.
2. The catalyst according to claim 1, characterized in that: The weight ratio of the active ingredient in component I to component II is 0.1-20; preferably 0.3-5.
3. The catalyst according to claim 1, characterized in that: The powder mixing method of component I and component II is to mix component I and component II by means of grinding, ball milling, etc., and to achieve uniform mixing by means of extrusion force, impact force, shearing force, friction force and other effects generated by the movement of materials and / or containers.
4. The catalyst according to claim 1, characterized in that: Component I further includes a dispersant, wherein the metal oxide is dispersed in the dispersant; the dispersant is Al2O3, SiO2, or Cr2O. 3、 One or more of ZrO2, TiO2, Ga2O3, activated carbon, graphene, and carbon nanotubes.
5. The catalyst according to claim 4, characterized in that: The content of dispersant in component I is 0.05-90 wt%, preferably 0.05-25 wt%, and the remainder is the metal oxide.
6. The catalyst according to claim 1, characterized in that: The silicon-modified low silica-to-alumina ratio ZSM-5 molecular sieve of component II has a silicon source of one or more of polysiloxane, water glass, sodium silicate, and tetraethyl orthosilicate.
7. The application of the catalyst according to claim 1 in the synthesis of aromatics from syngas, characterized in that: Aromatic hydrocarbons are produced by a conversion reaction using syngas as the reactant, which is an H2 / CO mixture, in the presence of a catalyst in a fixed-bed or moving-bed reactor. The H2 / CO molar ratio of the syngas is 0.2-3.5; the reaction pressure is 0.5-10 MPa; the reaction temperature is 300-600℃; and the reaction space velocity is 300-12000 h⁻¹. -1 .
8. The application according to claim 7, characterized in that: The reaction process can achieve an aromatic selectivity of 60-80%, and BTX can achieve a selectivity of 60% in aromatics, while the byproduct methane selectivity is less than 8%.